ANALYSIS OF WATER-COOLED ELECTRIC CHILLER AT DISTRICT COOLING PLANT - JA’AFAR, NUR SYAHIRAH (IRC, 2020)
Universiti Teknologi PETRONAS (UTP) uses district cooling (DC) system for air-conditioning purpose. The UTP GDC plant produces chilled water. Chilled water is produced by chiller namely the Electric Chiller (EC). This study investigated the performance of water-cooled electric chiller by evaluating Coefficient of Performance method (COP) under theoretical and actual operating conditions. Microsoft Excel spreadsheet software was used to evaluate the COP. Historical data from UTP GDC were used for analysis. Evaluated COP for the electric chiller varies from 3.12 to 7.11.